Radiological Imaging Picture Of Head Trauma Due To Violence In Children - Muh. Ridzky Afdal; Rahmawati, Rahmawati; Hamzakir, Hamzakir (Jurnal EduHealth, 2024)
In everyday life, violence is still often encountered. Child abuse is all forms of physical or emotional harm, sexual abuse, trafficking, neglect, exploitation resulting in injury Head trauma in children is one of the leading causes of death and disability. Of course, there are many considerations to perform the examination considering the risk of radiation that can interfere with the process of brain development for children < 2 years of age. CT scan is one of the radiological examination that is still often used today. This literature review aiming to determine the radiological imaging of head trauma due to violence in children. The method used was a literature review with a Narrative Reviews design to identify and summary previously published articles on the radiological imaging of head trauma due to child abuse. From the 20 articles summarized, the results showed that the radiological imaging of head trauma due to violence in children often occurred in boys and the most common CT scan radiological images were intracranial hemorrhage (subdural) hematoma, epidural hematoma, intracerebral hematoma.